Zero-dimensional mathematical model of the torch ignited engine. (25th June 2016) - Cruz, Igor William Santos Leal; Alvarez, Carlos Eduardo Castilla; Teixeira, Alysson Fernandes; Valle, Ramon Molina
Highlights: Publications about the torch ignition system are mostly CFD or experimental research. A zero-dimensional mathematical model is presented. The model is based on classical thermodynamic equations. Approximations are based on empirical functions. The model is applied to a prototype by means of a computer code. Abstract: Often employed in the analysis of conventional SI and CI engines, mathematical models can also be applied to engines with torch ignition, which have been researched almost exclusively by CFD or experimentally. The objective of this work is to describe the development and application of a zero-dimensional model of the compression and power strokes of a torch ignited engine. It is an initial analysis that can be used as a basis for future models. The processes of compression, combustion and expansion were described mathematically and applied to an existing prototype by means of a computer code written in MATLAB language. Conservation of energy and mass and the ideal gas law were used in determining gas temperature, pressure, and mass flow rate within the cylinder. Gas motion through the orifice was modelled as an isentropic compressible flow. The thermodynamic properties of the mixture were found by a weighted arithmetic mean of the data for each component, computed by polynomial functions of temperature. Combustion was modelled by the Wiebe function. Heat transfer to the cylinder walls was estimated by Annand's correlations. Results revealed the behaviour of pressure, temperature, jet velocity, energy transfer, thermodynamic properties, among other variables, and how some of these are influenced by others.